Schedule-dependent potentiation of chemotherapy drugs by the hypoxia-activated prodrug SN30000. Issue 9 (2nd September 2019) - Mao, Xinjian; McManaway, Sarah; Jaiswal, Jagdish K.; Hong, Cho R.; Wilson, William R.; Hicks, Kevin O.
ABSTRACT: Hypoxia-activated prodrugs (HAPs) are hypothesized to improve the therapeutic index of chemotherapy drugs that are ineffective against tumor cells in hypoxic microenvironments. SN30000 (CEN-209) is a benzotriazine di- N -oxide HAP that potentiates radiotherapy in preclinical models, but its combination with chemotherapy has not been explored. Here we apply multiple models (monolayers, multicellular spheroids and tumor xenografts) to identify promising SN30000/chemotherapy combinations (with chemotherapy drugs before, during or after SN30000 exposure). SN30000, unlike doxorubicin, cisplatin, gemcitabine or paclitaxel, was more active against cells in spheroids than monolayers by clonogenic assay. Combinations of SN30000 and chemotherapy drugs in HCT116/GFP and SiHa spheroids demonstrated hypoxia-and schedule-dependent potentiation of gemcitabine or doxorubicin in growth inhibition and clonogenic assays. Co-administration with SN30000 suppressed clearance of gemcitabine in NIH-III mice, likely due to SN30000-induced hypothermia which also modulated extravascular transport of gemcitabine in tumor tissue as assessed from its diffusion through HCT116 multicellular layer cultures. Despite these systemic effects, the same schedules that gave therapeutic synergy in spheroids (SN30000 3 h before or during gemcitabine, but not gemcitabine 3 h before SN30000) enhanced growth delay of HCT116 xenografts without increasing host toxicity. Identification of hypoxic and S-phase cells by immunohistochemistry and flow cytometry established that hypoxic cells initially spared by gemcitabine subsequently reoxygenate and re-enter the cell cycle, and that this repopulation is prevented by SN30000 only when administered with or before gemcitabine. This illustrates the value of spheroids in modeling tumor microenvironment-dependent drug interactions, and the potential of HAPs for overcoming hypoxia-mediated drug resistance.